Convegno PRIN 2013-2016 «Successo formativo, inclusione e coesione sociale: strategie innovative, ICT e modelli valutativi. Risultati della ricerca e nuove prospettive». Resoconto sintetico - Giovanni Moretti (LED Edizioni Universitarie, 2017)
The concluding conference of the national research project PRIN 2013-2016 entitled «Formative Success, Inclusion and Social Cohesion: Innovative Strategies, ICT and Evaluation Models. Research Results and New Perspectives» was be held in Rome, on the 17th and 18th of March 2017 at the Department of Education, University Roma Tre. The congress has represented the milestone of a three-year interdisciplinary research project, attended by seven italian universities: the University Rome Tre (leader of the project) and the University of Turin, Verona, Bologna, Rome Sapienza, Foggia and Palermo. During the conference, the overall and specific outcomes obtained by each work units were presented. The PRIN project has allowed significant evidences of some of the preconditionsthat can allow teachers and schools to employ coherently and effectively innovative teaching strategies, ICT, and to apply evaluation models, in particula the formative evaluation system. The themes of self-assessment and orientation were also addressed in the perspective of promoting educational success, school and social inclusion. A specific attention was given to the problem related to orientation strategies and university-work transition.